Preventing Germinal Matrix Layer Rupture and Intraventricular Hemorrhage - Coen, Ronald W. (Frontiers in Pediatrics, 2013)
The etiology of intraventricular hemorrhage in extremely low birth weight preterm infants is multifactorial with circulatory instability and hemostasis being preeminent. This study sought to determine if the germinal matrix layer remained intact when platelets were above 200 X109/L, a near normal level, and fell below that when intraventricular hemorrhages occurred. This was a retrospective study of platelets and head ultrasounds in infants 23 to 28 weeks gestation. Analyses were descriptive, one way analysis of variance, Pearson Chi-square tests and t-tests. Platelet counts and head ultrasounds were linked in 114 infants during the first 3 days when 90% of intraventricular hemorrhages occur. Mean platelet levels were > 200 X 109/L in 68% of infant 23 – 24 weeks gestation and 78% of those 25 -26 weeks when there were no intraventricular hemorrhages. These findings, if confirmed, suggest that improving hemostasis in high risk preterm infants by keeping platelet levels >200 X109/L may maintain the integrity of the germinal matrix layer and prevent intraventricular hemorrhages.